Blood profiles in elite cross-country skiers: a 6-year follow-up - Morkeberg, J.; Saltin, B.; Belhage, B.; Damsgaard, R. (Scandinavian Journal of Medicine & Science in Sports, 2009)
Following the doping scandals at the World Championships in cross-country skiing in 2001, the International Ski Federation decided to generate individual blood profiles. From 2001 to 2007, 7081 blood samples from 1074 male and female elite cross-country skiers were collected and analyzed for hemoglobin concentration [Hb] and % reticulocytes (%rets). Data were applied to blood algorithms wherefrom blood model scores were calculated. From 1997-1999 to 2001-2002, the mean [Hb] was reduced by 0.9 g/dL to 15.3 g/dL in male skiers and by 0.4 g/dL to 13.8 in female skiers. From 2002-2003 to 2006-2007, the combination of increases in [Hb] and decreases in %rets led to pronounced increases in mean OFF-model scores. [Hb] was 0.2 g/dL higher at Olympic Games/World Championships (WOCs) than at World Cups competitions <4 weeks before and after WOCs. [Hb] and %rets increased with altitude in both genders. Since the introduction of an enlarged blood testing program, the mean [Hb] values were lowered to close to normal levels, but over the last 2-3 years there has been a small elevation and an increase in OFF-model scores, which may indicate a change in the manipulations used to elevate the [Hb].